Cardiac surgeons' concerns, perceptions, and responses during the COVID‐19 pandemic. Issue 9 (12th June 2021) - Luc, Jessica G.Y.; Ad, Niv; Nguyen, Tom C.; ,; Arora, Rakesh C.; Balkhy, Husam H.; Bender, Edward M.; Bethencourt, Daniel M.; Bisleri, Gianluigi; Boyd, Douglas; Chu, Michael W.A.; de la Cruz, Kim I.; et al.
Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic has had an unprecedented impact on health care and cardiac surgery. We report cardiac surgeons' concerns, perceptions, and responses during the COVID‐19 pandemic. Methods: A detailed survey was sent to recruit participating adult cardiac surgery centers in North America. Data regarding cardiac surgeons' perceptions and changes in practice were analyzed. Results: Our study comprises 67 institutions with diverse geographic distribution across North America. Nurses were most likely to be redeployed (88%), followed by advanced care practitioners (69%), trainees (28%), and surgeons (25%). Examining surgeon concerns in regard to COVID‐19, they were most worried with exposing their family to COVID‐19 (81%), followed by contracting COVID‐19 (68%), running out of personal protective equipment (PPE) (28%), and hospital resources (28%). In terms of PPE conservation strategies among users of N95 respirators, nearly half were recycling via decontamination with ultraviolet light (49%), followed by sterilization with heat (13%) and at home or with other modalities (13%). Reuse of N95 respirators for 1 day (22%), 1 week (21%) or 1 month (6%) was reported. There were differences in adoption of methods to conserve N95 respirators based on institutional pandemic phase and COVID‐19 burden, with higher COVID‐19 burden institutions more likely to resort to PPE conservation strategies. Conclusions: The present study demonstrates the impact of COVID‐19 on North American cardiac surgeons. Our study should stimulate further discussions to identify optimal solutions to improve workforce preparedness for subsequent surges, as well as facilitate the navigation of future healthcare crises.